2017
DOI: 10.1108/ijshe-10-2015-0169
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perception of sustainability orientation within a major Romanian University

Abstract: Purpose The research attempts to aim to evaluate the perception that different stakeholder groups have of one of the largest and most important Romanian university with respect to its sustainability orientation. The exploratory empirical research reveals some important aspects which must be closely pursued and properly implemented by the management of the university to further develop sustainability strategies. The paper offers a novel approach regarding the way a university can and must focus on different spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
1
39
0
1
Order By: Relevance
“…As sheer institutionalized relationships often lack flexibility and rapid adjustments, more dynamic social aggregations have sprung to support trans-organizational knowledge renewal by means of inter-organizational learning, good practices and access to the work of reputed scholars in different fields [5]. Built on the foundations of the digital era and of the network society [6][7][8][9][10][11][12] with a view to support the transformation of adaptive to generative learning [13][14][15], online academic networks have set the scene for new patterns of knowledge access, exchange, transfer, diffusion, discovery and so forth. Progressively, under the aegis of the Internet which "facilitates circulation of knowledge" and reframes collaboration among peers [16], online academic networks emerged as knowledge brokers for various categories of stakeholders, putting up a stronger rationale in terms of knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…As sheer institutionalized relationships often lack flexibility and rapid adjustments, more dynamic social aggregations have sprung to support trans-organizational knowledge renewal by means of inter-organizational learning, good practices and access to the work of reputed scholars in different fields [5]. Built on the foundations of the digital era and of the network society [6][7][8][9][10][11][12] with a view to support the transformation of adaptive to generative learning [13][14][15], online academic networks have set the scene for new patterns of knowledge access, exchange, transfer, diffusion, discovery and so forth. Progressively, under the aegis of the Internet which "facilitates circulation of knowledge" and reframes collaboration among peers [16], online academic networks emerged as knowledge brokers for various categories of stakeholders, putting up a stronger rationale in terms of knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…"The present structure of the teacher training system can be described as a good practice example concerning higher education professional development or as an alternative that is worthy to be taken into consideration for other countries with similar educational systems or by countries/universities that believe that pedagogical training addressing ESD should be completed early in one's teaching career" [41]. "Stakeholders expressed highly favourable opinions of the university's dealings with different sustainability aspects … its establishment of an attractive and innovative educational programme, in compliance with sustainability principles, environmental protection and modern attitudes towards society" [42] "The efforts still required to be made are significant, since it is observed that all undergraduate, postgraduate and PhD require a change of attitude and mentality" [40]. "The present Romanian teacher training curriculum does not nurture ESD competencies, and it does not have this purpose at all" [41].…”
Section: Romaniamentioning
confidence: 99%
“…Nowadays, the fundamental task of universities is to generate knowledge through education, development of research and interaction (Deaconu and Nistor, 2017) with the local economic and social environment, and to transfer it to the industry (Urdari, Farcas and Tiron-Tudor, 2017). In this way, universities, alongside other local and regional players contribute to regional economic development (Dabija et al, 2017).…”
Section: Bio-economy and Universities' Activitiesmentioning
confidence: 99%
“… Sustainability -In the last decades, we have witnessed at the development of the sustainability concept encompassing the development and creation of an organisation's longterm value basing on innovation as well as intellectual and relation capital. In this context, public institutions have increasingly embraced the sustainable development discourse (Dabija et al, 2017) thus becoming dynamically involved in developing public policies that encourage social responsibility and accountability. According to prior evidence, more socially responsible universities have a higher web-disclosure index (Bisogno et al, 2014), which led us to the assumption that sustainability is also a potential explanatory factor able to influence the level of the IC disclosure positively.…”
Section: Sample Selection and Variable Measurementmentioning
confidence: 99%